Comparison of the effect of infrared (IR) and Phenytoin cream on skin wound healing in rat - R Tavakoli (Babol University of Medical Sciences, 2004)
Background and Objective: Infrared (IR) is one of the modalities in electrotherapy that indicates for treatment of some diseases with minimal side effects, but there is different ideas about its effects on wound healing. The aim of this study was to investigate effects of IR on skin wound healing in rat and its comparison with phenytoin’s effect. Methods: This interventional and experimental study was done on three groups of rats. After inducing general anesthesia in rats, skin wound was made on dorsal neck about 2 cm². Then from third day after operation, IR and phenytoin cream (1%) were indicated in two groups. No treatment was administered for control group. Wound surface area, percentage of recovery and rat weight change post operation at 1st, 4th, 7th and 10th day were measured. Number of fibroblasts, collagen fibers, new vessels, lymphocytes, macrophages, neutrophils and thickness of epiderm were determined in three groups by biopsy at 10th day. Findings: The results showed that percentage of recovery was not significantly different in three groups at 4th day. But, percentage of recovery at 7th day in IR, control and phenytoin group were 51.5±17.7, 38.8±17.9 and 55.3±10.1, respectively (P<0.04) and at 10th day in IR, control and phenytoin group were 68.4±17.5, 57±18.4 and 78.9±8.2, respectively (P<0.01). Number of new vessels, fibroblasts, macrophages, lymphocytes, neutrophils and thickness of epiderm were not significantly different in three groups after 10th days. Number of collagen fibers was significantly different in three groups (P<0.01). Conclusion: Findings suggest that infrared accelerates wound healing from 7th day that this effect is the same as phenytoin’s healing effect.